Answer:
Please what are you trying to say
Answer:
4800$
Step-by-step explanation:
1 day = 600
7 years = 600 x 2 = 1200$
14 years = 1200 x 2 = 2400$
21 years = 2400 x 2 = 4800$
Answer:
A ≈ 9.0 ft²
Step-by-step explanation:
70° = 7π/18 radians
Area of the arc section
A = ½(7π/18)8² = 12⁴/₉π ft² = 39.09537 ft²
As the triangle is isosceles, the other two angles are (180 - 70) / 2 = 55°
law of sines 8 / sin55 = L / sin 70 L = 9.17722
so the triangle height = √(8² - (9.17722/2)²) = 6.55321
Area of triangle ½(6.55321)(9.17722) = 30.07016
Area = 39.09537 - 30.07016 = 9.025211 ≈ 9.0 ft²
<span>Integral of 1/(x^2sqrt(4x+1)) = 4tanh^-1(sqrt(4x + 1)) - sqrt(4x + 1) / x + c</span>
Answer:
![a=-23\\\\b=28](https://tex.z-dn.net/?f=a%3D-23%5C%5C%5C%5Cb%3D28)
Step-by-step explanation:
Let's start by using distributive multiplication:
![(a\pm b)(c\pm d)=ac\pm ad \pm bc \pm bd](https://tex.z-dn.net/?f=%28a%5Cpm%20b%29%28c%5Cpm%20d%29%3Dac%5Cpm%20ad%20%5Cpm%20bc%20%5Cpm%20bd)
So:
![(5x-4)(3x+7)=15x^2+35x-12x-28\\\\](https://tex.z-dn.net/?f=%285x-4%29%283x%2B7%29%3D15x%5E2%2B35x-12x-28%5C%5C%5C%5C)
Grouping like terms:
![15x^2 +(35x-12x)-28\\\\15x^2+23x-28](https://tex.z-dn.net/?f=15x%5E2%20%2B%2835x-12x%29-28%5C%5C%5C%5C15x%5E2%2B23x-28)
Now,
is equal to:
![15x^2-ax-b](https://tex.z-dn.net/?f=15x%5E2-ax-b)
In this sense:
![15x^2+23x-28=15x^2-ax-b](https://tex.z-dn.net/?f=15x%5E2%2B23x-28%3D15x%5E2-ax-b)
In order to satisfied the equality:
![23x=-ax\hspace{10}(1)\\\\and\\\\-28=-b\hspace{10}(2)](https://tex.z-dn.net/?f=23x%3D-ax%5Chspace%7B10%7D%281%29%5C%5C%5C%5Cand%5C%5C%5C%5C-28%3D-b%5Chspace%7B10%7D%282%29)
Hence, from (1), let's solve for a:
![23x=-ax\\\\-a=\frac{23x}{x} \\\\-a=23\\\\a=-23](https://tex.z-dn.net/?f=23x%3D-ax%5C%5C%5C%5C-a%3D%5Cfrac%7B23x%7D%7Bx%7D%20%5C%5C%5C%5C-a%3D23%5C%5C%5C%5Ca%3D-23)
And from (2), let's solve for b:
![-28=-b\\\\b=28](https://tex.z-dn.net/?f=-28%3D-b%5C%5C%5C%5Cb%3D28)
Let's verify the result evaluating the values of a and b into the original equation:
![(5x-4)(3x+7)=15x^2+23x-28=15x^2 -ax -b\\\\(5x-4)(3x+7)=15x^2+23x-28=15x^2 -(-23)x -(28)\\\\(5x-4)(3x+7)=15x^2+23x-28=15x^2 +23x -28](https://tex.z-dn.net/?f=%285x-4%29%283x%2B7%29%3D15x%5E2%2B23x-28%3D15x%5E2%20-ax%20-b%5C%5C%5C%5C%285x-4%29%283x%2B7%29%3D15x%5E2%2B23x-28%3D15x%5E2%20-%28-23%29x%20-%2828%29%5C%5C%5C%5C%285x-4%29%283x%2B7%29%3D15x%5E2%2B23x-28%3D15x%5E2%20%2B23x%20-28)
As you can see, the values satisfy the equation, therefore, we can conclude they are correct.